Determinants of share price - special reference with the hotel and travel industry in Sri Lanka - Tharshiga, P.; Subramaniam, V.A. (University of Jaffna, 2023)
Knowledge of the dynamism of stock indices is essential to the future projection of stock performance and, in turn, provides a basis for appointing and suggesting appropriate economic policies. This study attempts to analyse the relationship between share price and share price determinants in Sri Lanka's hotel and travel industry. To achieve the objectives of the study, 33 companies in the hotel and tourism industry were selected from 2015/2016 to 2019/2021. Descriptive statistics, unit root tests, pooled ordinary least squares regression, fixed effects and random effects analysis are used to analyze data. The results of the Hausman test show that the fixed model is a better estimate than the random effect model. Dividend per share and earnings per share have a strong positive significance relationship with the price of the share. Dividend yields and ROE have a significant negative relationship with dine prices. Other variables, such as dividend payments, leverage and ROA have no statistically significant relationship with share prices. The present study confirms that internal factors such as DPS and EPS have strong explanation power in determining the share price of the company. Most research studies conducted on the assessment of valuable notes also highlighted EPS and DPS as major variables in share value and paid less attention to other variables. As a result, investors and shareholders take into account this recent variation in their decisions.
Keywords: Dividend per share; Earning per share; Dividend yield; Leverage; Share price